Adhesive bonding of resin composite to various titanium surfaces using diferente metal conditioners and a surface modification system - Almilhatti, Hercules Jorge; Neppelenbroek, Karin Hermana; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Giampaolo, Eunice Teresinha [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2013)
Objective: This study evaluated the effect of three metal conditioners on the shear bond strength (SBS) of a prosthetic composite material to cpTi grade I having three surface treatments. Material and Methods: One hundred sixty eight rivet-shaped specimens (8.0x2.0 mm) were cast and subjected to polishing (P) or sandblasting with either 50 mu m (50SB) or 250 mu m (2505B) Al2O3. The metal conditioners Metal Photo Primer (MPP), Cesead II Opaque Primer (OP), Targis Link (TL), and one surface modification system Siloc (S), were applied to the specimen surfaces, which were covered with four 1-mm thick layers of resin composite. The resin layers were exposed to curing light for 90 s separately. Seven specimens from each experimental group were stored in water at 37 degrees C for 24 h while the other 7 specimens were subjected to 5,000 thermal cycles consisting of water baths at 4 degrees C and 60 degrees C (n=7). All specimens were subjected to SBS test (0.5 mm/min) until failure occurred, and further 28 specimens were analyzed using scanning electron microscope (SEM) and X-ray energy-dispersive spectroscopy (EDS). Data were analyzed by 3-way ANOVA followed by post-hoc Tukey's test (alpha=0.05). Results: On 50SB surfaces, OP groups showed higher SBS means than MPP (P<0.05), while no significant difference was found among OP, 5, and TL groups. On 2505B surfaces, OP and TL groups exhibited higher SBS than MPP and S (P<0.05). No significant difference in SBS was found between OP and TL groups nor between MPP and S groups. The use of conditioners on 250SB surfaces resulted in higher SBS means than the use of the same products on 50SB surfaces (P<0.05). Conclusion: Sandblasting associated with the use of metal conditioners improves SBS of resin composites to cpTi.
Keywords: Dental materials; Dental alloys; Composite resins; Dental prosthesis